Florestan Fernandes: a autocracia burguesa como estrutura histórica e a institucionalização da contra-revolução no Brasil - Chagas, Rodrigo Pereira (2011)
The object of this study is to examine, within the framework of the ideology upheld by the Sociologist Florestan Fernandes (1920-1995), his understanding of the process commonly known as transition or political opening in Brazil (1974-1988) where he participated as a privileged agent, setting forth a highly elaborated analysis of Brazilian social structures and functioning as an organic intellectual dos de baixo in activities such as: professor, publicist and deputy. Within this framework, we visualize an intense and promising activity but often leading to deep disappointment that discourage the institutionalization of the military dictatorship (counter-revolution) in Brazil and the preservation of archaic structures through conservative modernization , combined with the systematic repression and refrain from popular participation in the nation s destiny . This study emphasizes two aspects that reflect Florestan Fernandes´ ideas: it examines some structural theoretical concepts, particularly, his conception of bourgeois autocracy on the one hand; and introduces his theoretical-practical facet that corresponds with the dynamic history of the struggle of classes